Labour unionisation structure and product innovation - Basak, Debasmita; Mukherjee, Arijit (Elsevier, 2018)
This paper contributes to the recently growing literature by examining the effects of different labour unionisation structures on innovation. Using a Cournot duopoly set up, we investigate the effects of centralised and decentralised labour unions on product innovation. We show that if the products are symmetrically differentiated, the incentive for innovation is higher under decentralised labour unions, whereas the innovation incentive can be higher under a centralised labour union if the products are asymmetrically differentiated. Our results show that social welfare is strictly higher under decentralised unions compared to a centralised union.